2021
DOI: 10.21203/rs.3.rs-703538/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A retrospective observational study of Chlorine Dioxide effectiveness to covid19-like symptoms prophylaxis in relatives living with COVID19 patients

Abstract: To date, there is no effective prophylactic agent to prevent COVID-19. However, the development of symptoms similar to covid19 could be prevented with an aqueous solution of chlorine dioxide (ClO2). This retrospective study evaluated the effectiveness of an aqueous solution of ClO2 (CDS) as a prophylactic agent in 1,163 family members living with positive/suspected COVID19 patients. Prophylactic treatment consisted of 0.0003% chlorine dioxide solution (CDS) orally for at least fourteen days. Family members in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…2). Aparicio-Alonso et al reported that oral administration of ClO 2 at 3 ppm in a dose of 0.3 mg/kg/ day was safe (9). Assuming the body weight of an adult is 50 kg, oral consumption of 15 mg/day ClO 2 is safe.…”
Section: Deduction Of An Appropriate Dose Of Clo 2 For Nasal Irrigationmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Aparicio-Alonso et al reported that oral administration of ClO 2 at 3 ppm in a dose of 0.3 mg/kg/ day was safe (9). Assuming the body weight of an adult is 50 kg, oral consumption of 15 mg/day ClO 2 is safe.…”
Section: Deduction Of An Appropriate Dose Of Clo 2 For Nasal Irrigationmentioning
confidence: 99%
“…). Aparicio-Alonso et al orally administered ClO 2 at 3 ppm as a prophylactic agent to family members living with COVID-19 patients in Mexico(9). They found that ClO 2 was effective at preventing COVID-19, and no adverse events were reported.…”
mentioning
confidence: 99%
“…They contend that such nasal irrigation may "wash out the nasal cavity", helping to reduce the viral load in the upper respiratory tract and thereby ameliorating COVID-19-related symptoms. Studies in Mexico even orally administered chlorine dioxide (ClO 2 ) in a low dose to prevent/treat COVID-19-related symptoms in relatives living with COVID-19 patients (7,8). iii) Alleviation of symptoms using natural products: This scenario includes a number of natural products such as Indonesian herbal compounds (9), Iran herbal medicine (10), propolis and honey (11), Indian herbs (12), essential oils (13), and traditional Chinese medicine (TCM) (14)(15)(16).…”
Section: Editorialmentioning
confidence: 99%